Student's Perception of Computer Based Assessment Environment in an Undergraduate Medical College - Kinza Aslam; Syed Hussain Raza Zaidi; Tayyaba Azhar; Fatima Zia Zaidi; Maimoona Nasreen (Shalamar Medical & Dental College, Lahore, Pakistan, 2023)
Background: It is emphasized in medical education that assessment drives learning. In 2020, during the first COVID-19 lockdown, University College of Medicine and Dentistry made a shift towards Computer Based Assessments (CBAs) in order to facilitate learning. Objective: To determine undergraduate medical student's perception for computer based assessment environment in medical school Methods: The cross-sectional descriptive study was conducted at the University of Lahore, Pakistan, from May 2022 to September 2022, and included undergraduate medical students who were requested to complete the Assessment Environment Questionnaire. Students' individual perception scores were calculated and the means of individual domains and global scores were compared in different academic years. SPSS version 23 was used for statistical analysis.   Results: Of 574 participants, 20% of the participants were from 1st year, 20.7% were from second year, 20% from 3rd year, 19.9% from 4thyear and 19.3% from final year. Generally, the students perceived their assessment environment positive resulting in a global mean score of 67.6±13.7 out of the maximum 80. First year students scored significantly higher (P <0.01) compared to other years. Conclusion: The students' perception for computer based assessment environment was positive